Genomic Selection for Processing and End‐Use Quality Traits in the CIMMYT Spring Bread Wheat Breeding Program - Battenfield, Sarah D.; Guzmán, Carlos; Gaynor, R. Chris; Singh, Ravi P.; Peña, Roberto J.; Dreisigacker, Susanne; Fritz, Allan K.; Poland, Jesse A. (The plant genome, 2016)
Core Ideas Genomic selection applied for wheat quality in CIMMYT spring bread wheat breeding program. All wheat quality traits predicted and validated using forward genomic selection. Dough and loaf traits have moderately high predictive ability in CIMMYT breeding program. Genomic selection genetic gain 1.4 to 2.7 times higher than phenotypic selection. Wheat (Triticum aestivum L.) cultivars must possess suitable end‐use quality for release and consumer acceptability. However, breeding for quality traits is often considered a secondary target relative to yield largely because of amount of seed needed and expense. Without testing and selection, many undesirable materials are advanced, expending additional resources. Here, we develop and validate whole‐genome prediction models for end‐use quality phenotypes in the CIMMYT bread wheat breeding program. Model accuracy was tested using forward prediction on breeding lines (n = 5520) tested in unbalanced yield trials from 2009 to 2015 at Ciudad Obregon, Sonora, Mexico. Quality parameters included test weight, 1000‐kernel weight, hardness, grain and flour protein, flour yield, sodium dodecyl sulfate sedimentation, Mixograph and Alveograph performance, and loaf volume. In general, prediction accuracy substantially increased over time as more data was available to train the model. Reflecting practical implementation of genomic selection (GS) in the breeding program, forward prediction accuracies (r) for quality parameters were assessed in 2015 and ranged from 0.32 (grain hardness) to 0.62 (mixing time). Increased selection intensity was possible with GS since more entries can be genotyped than phenotyped and expected genetic gain was 1.4 to 2.7 times higher across all traits than phenotypic selection. Given the limitations in measuring many lines for quality, we conclude that GS is a powerful tool to facilitate early generation selection for end‐use quality in wheat, leaving larger populations for selection on yield during advanced testing and leading to better gain for both quality and yield in bread wheat breeding programs.